2018
DOI: 10.1029/2018gl079834
|View full text |Cite
|
Sign up to set email alerts
|

A Bimaterial Interface Along the Northern San Jacinto Fault Through Cajon Pass

Abstract: We investigate the existence of bimaterial interfaces along the San Jacinto fault zone (SJFZ) and the San Andreas fault (SAF) around their intersection at Cajon Pass (CP) to clarify if large earthquakes can rupture simultaneously parts of both faults. Analysis of fault zone head waves reveals a bimaterial interface along the northern SJFZ with a >7.5% velocity contrast (slower northeast side) that extends continuously through and perhaps slightly beyond CP. Other seismological studies show an opposite sense of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…This agrees well with the observation of velocity contrast reversal across the SAF northwest and southeast of the SGP (Share & Ben‐Zion, ), The Vs around the ECSZ is much slower after the inversion, particularly for the region north to SGP for depths from 5 to 10 km (Figure ), which corresponds well with the area that has large damage volume in Ben‐Zion and Zaliapin (). The Salton Trough is imaged with a well‐defined shape of LVZ extended to depth 7 km in our final Vs model. Compared to the initial model, the velocities are much slower (~0.3 km/s) in the top 3–7 km. Different from the initial model, a clear shift in the velocity contrast interface location is observed by comparing Vs at 10 and 15 km for our final Vs model at the south SAF (Figure ), indicating a northeast dipping fault plane. The highest velocities are observed in the Peninsular Ranges, and a sharp velocity contrast from west to east at greater depth (7–15 km; white vertical line in Figure ) that corresponds to the Hemet stepover (Marliyani et al, ) is observed much clearly in the final model. Velocity contrasts across major faults (e.g., SAF and SJF) previously imaged in other tomography (e.g., Fang et al, ; Share et al, ) and fault zone head wave studies (Share & Ben‐Zion, , ) are observed clearly in the final Vs model.…”
Section: Shear Wave Velocity Inversionmentioning
confidence: 72%
“…This agrees well with the observation of velocity contrast reversal across the SAF northwest and southeast of the SGP (Share & Ben‐Zion, ), The Vs around the ECSZ is much slower after the inversion, particularly for the region north to SGP for depths from 5 to 10 km (Figure ), which corresponds well with the area that has large damage volume in Ben‐Zion and Zaliapin (). The Salton Trough is imaged with a well‐defined shape of LVZ extended to depth 7 km in our final Vs model. Compared to the initial model, the velocities are much slower (~0.3 km/s) in the top 3–7 km. Different from the initial model, a clear shift in the velocity contrast interface location is observed by comparing Vs at 10 and 15 km for our final Vs model at the south SAF (Figure ), indicating a northeast dipping fault plane. The highest velocities are observed in the Peninsular Ranges, and a sharp velocity contrast from west to east at greater depth (7–15 km; white vertical line in Figure ) that corresponds to the Hemet stepover (Marliyani et al, ) is observed much clearly in the final model. Velocity contrasts across major faults (e.g., SAF and SJF) previously imaged in other tomography (e.g., Fang et al, ; Share et al, ) and fault zone head wave studies (Share & Ben‐Zion, , ) are observed clearly in the final Vs model.…”
Section: Shear Wave Velocity Inversionmentioning
confidence: 72%
“…Most events in the central San Jacinto fault zone have directivities to the northwest, while most events around Cajon Pass and San Gabriel Mountain have directivities to the southeast. The observations imply that the ruptures tend to propagate in the direction of motion of slow sides of the imaged velocity contrasts (e.g., Allam & Ben‐Zion, ; Zigone et al, ; Share & Ben‐Zion, ; Share, Allam, et al, ). These results are generally consistent with expectations for dynamic rupture on a bimaterial interface (e.g., Ampuero & Ben‐Zion, ; Andrews & Ben‐Zion, ; Ben‐Zion, ; Brietzke & Ben‐Zion, ; Ranjith & Rice, ; Shlomai & Fineberg, ; Weertman, ).…”
Section: Discussionmentioning
confidence: 98%
“…(2004) propose that the geometry and path of the present‐day SJF was dictated by a preexisting physical property contrast and that earthquakes on the fault continue to nucleate along this discontinuity. Detailed seismic imaging studies show that the main strike‐slip faults in Southern California are associated with prominent lithology contrasts (e.g., Fang et al., 2016; Qiu et al., 2019; Share & Ben‐Zion, 2016, 2018; Share et al., 2019). Here, we take this concept of inheritance further and propose that the Southern California region contains a pervasive rock fabric throughout the lithosphere.…”
Section: Discussion: the Importance Of Fault And Fabric Reactivation mentioning
confidence: 99%